High-tear-resistance low-smoke halogen-free sheath material as well as preparation method and application thereof
By adopting a specific resin system and flame retardant combination in the cable sheath material and combining advanced processing technology, the existing materials have solved the problem of taking into account the tear resistance, mechanical properties and flame retardant properties, and high-performance cable sheath material is achieved.
Patent Information
- Application Number
- CN202411457456.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-28
AI Technical Summary
While existing cable sheath materials are highly tear-resistant, low smoke and halogen-free, the flame retardant performance and mechanical properties are difficult to take into account, and cracking, low elongation and poor flame retardant performance are prone to problems.
A resin system combined with ethylene propylene ternary rubber, octacarbon polyolefin elastomer, metallocene catalytic linear low-density polyethylene and maleic anhydride grafted polyethylene is adopted, and a flame retardant system of inorganic flame retardant, silicone flame retardant and nanowhisker-forming carbon agent is used to prepare a high tear-resistant, low smoke and halogen-free sheath material through the processing technology of the mixer and the extruder.
It has achieved high tear resistance and improved mechanical properties, and has excellent flame retardant properties, suitable for the use of large-sized cables, and has stable product quality and reaches the leading level in China.
Smart Images

Figure BDA0005090882740000011 
Figure BDA0005090882740000101 
Figure FDA0005090882730000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sheath material preparation, and in particular relates to a high tear resistance, low smoke, halogen-free sheath material and a preparation method and application thereof. Background Art
[0002] The international community has increasingly stringent requirements for cable safety. High-speed railways, ships, nuclear power plants, and large venues basically use large-size cables to transmit electricity. In such narrow venues, the tear resistance of the cable sheath is very important. Because the expansion coefficient of the base material and the inorganic flame retardant is quite different, uneven shrinkage is prone to occur, resulting in structural defects, leading to cracking of wires and cables.
[0003] At present, the large-scale cable material manufacturers in China are conducting research on high tear resistance low smoke zero halogen polyolefin sheath materials. Products that can pass the high tear resistance test are basically made of polyethylene materials with a large amount of polyethylene. Due to the high strength of polyethylene and poor coating of inorganic powder flame retardants, this will affect the compatibility of flame retardants with polyethylene substrates, resulting in cracking, low elongation, poor flame retardant performance, etc. Summary of the invention
[0004] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0005] During the debugging process, we tried adding a resin system composed of EPDM rubber, eight-carbon polyolefin elastomer, metallocene-catalyzed linear low-density polyethylene, and maleic anhydride grafted polyethylene; a flame retardant system composed of inorganic flame retardants, silicone flame retardants, and nanowhisker carbonizing agents. The combination of the above two systems can simultaneously achieve better mechanical properties and flame retardant properties.
[0006] The present invention provides a high tear resistance low smoke halogen-free sheath material, which is prepared by the following raw materials in parts by weight:
[0007]
[0008]
[0009] The carbon-forming agent includes hydrated magnesium silicate nano whiskers; the organic composite flame retardant is obtained by melt blending a siloxane copolymer containing polycarbonate, an organic ammonium salt, a linear low-density polyethylene and calcium carbonate;
[0010] During the melt blending, the internal mixing temperature is 120° C. and the single screw extruder is used for extrusion granulation at 90-110° C.; the organic ammonium salt is selected from ammonium phosphate and ammonium polyphosphate.
[0011] In the organic composite flame retardant, the mass ratio of the polycarbonate-containing siloxane copolymer, the organic ammonium salt, the linear low-density polyethylene and the calcium carbonate is 1:1:3:75.
[0012] The linear low-density polyethylene is selected from Japan Prime SP1520, Exxon 3518CB or LG Chemical 3518CN.
[0013] The maleic anhydride grafted polyethylene is selected from Nengzhiguang MC226 or Juding 2002.
[0014] The hydrated magnesium silicate nano whiskers are selected from hydrated magnesium silicate nanofibers of whetstone mineral fiber, and the model is Adins Clay 20.
[0015] The lubricant type is Struktol TR451.
[0016] Preferably, the EPDM rubber further contains 4-6 wt % of 5-ethylidene-2-norbornene.
[0017] Preferably, the organic ammonium salt is selected from ammonium phosphate and ammonium polyphosphate.
[0018] Preferably, in the organic composite flame retardant, the mass ratio of the polycarbonate-containing siloxane copolymer, the organic ammonium salt and the linear low-density polyethylene is 2:2:6.
[0019] Preferably, the antioxidant is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and dilauryl thiodipropionate (DLTP).
[0020] Furthermore, the mass ratio of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate is 7:3.
[0021] The present invention also provides a method for preparing the above-mentioned high tear resistance low smoke halogen-free sheath material, comprising the following steps:
[0022] S1: Mixing and plasticizing the raw materials in an internal mixer to obtain processed materials;
[0023] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles;
[0024] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0025] Preferably, in step S1, the temperature of mixing and plasticizing in the internal mixer is 155-165° C., and the time of mixing and plasticizing is 12-18 min.
[0026] Preferably, in step S2, the temperature of zones 1 to 12 of the twin-screw extruder during extrusion is 90-120°C.
[0027] Preferably, in step S2, the temperature of the single screw extruder during granulation is 120-150° C., and the pelletizing frequency of the single screw extruder is 1200 Hz.
[0028] The present invention aims to invent a cable sheath material suitable for large square cables, which has high tear resistance, processing performance, mechanical properties and flame retardant properties, stable quality, and the product technology level reaches the domestic leading level. Because for large-sized wires and cables, materials, structures, installation methods, and bending radius have a significant impact on cracking. At present, most solutions are to reduce the amount of flame retardants in the formula to enhance the mechanical properties of the cable, but the small amount of flame retardant added will cause problems such as reduced flame retardant performance and substandard cable combustion performance.
[0029] The present invention also provides a cable sheath, which is prepared by using the above-mentioned high tear resistance low smoke halogen-free sheath material.
[0030] The technical solution of the present invention has the following advantages over the prior art:
[0031] The experimental results show that the tear resistance and mechanical properties of the product produced by the present invention are superior to those of traditional materials:
[0032] (1) EPDM rubber replaces part of conventional EVA materials: high Mooney value leads to improved physical and mechanical properties after high filling; 5% ethylene-norbornene's corrosion resistance, water vapor resistance, hot water resistance, elasticity, and adhesion ensure the excellent performance of the finished product;
[0033] (2) Eight-carbon polyolefin elastomer replaces linear low-density polyethylene, and the mechanical properties (elongation, resistance to thermal stress cracking) of the material are significantly improved, and the tear strength is also improved;
[0034] (3) Hydrated magnesium silicate nanofibers and halogen-free metal hydroxide flame retardants form a highly efficient flame retardant synergistic effect, promoting the polymer to form a denser ceramic layer, with rapid shell and ceramic formation properties, reducing smoke density, limiting the spread of fire and reducing heat and smoke release;
[0035] (4) Organic compound flame retardants significantly increase the oxygen index and improve combustion performance;
[0036] In addition to achieving the high tear strength of tear-resistant products, the patented product also has excellent mechanical properties suitable for the normal use and laying requirements of cables, as well as high flame retardant properties. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0038] Example 1
[0039] The high tear resistance low smoke zero halogen sheath material of this embodiment is prepared by the following raw materials in parts by weight:
[0040] 15 parts of ethylene vinyl acetate (EVA);
[0041] 5 parts of ethylene propylene diene monomer (EDPM), wherein the ethylene propylene diene monomer further contains 5 wt % of 5-ethylidene-2-norbornene;
[0042] 10 parts of linear low-density polyethylene (LLDPE), wherein the linear low-density polyethylene is selected from Japan Pu Ruiman SP1520;
[0043] 4 parts of eight-carbon polyolefin elastomer (eight-carbon POE);
[0044] 6 parts of Nengzhiguang MC226 maleic anhydride grafted polyethylene;
[0045] 80 parts of aluminum hydroxide and 8 parts of magnesium hydroxide;
[0046] 2 parts of carbon forming agent hydrated magnesium silicate nano whisker, the hydrated magnesium silicate nano whisker is selected from whetstone mineral fiber hydrated magnesium silicate nanofiber, model is Adins Clay 20;
[0047] 0.8 parts of an organic composite flame retardant, which is obtained by melt blending a polycarbonate-containing siloxane copolymer, an organic ammonium salt, a linear low-density polyethylene and calcium carbonate in a mass ratio of 1:1:3:75; the organic ammonium salt is selected from ammonium phosphate and ammonium polyphosphate; during melt blending, the mixer has a mixer temperature of 120°C and is extruded and granulated at 100°C using a single screw extruder.
[0048] 0.5 parts of an antioxidant, specifically pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate (DLTP) in a mass ratio of 7:3;
[0049] 0.4 parts of lubricant Struktol TR451.
[0050] The preparation method of the above-mentioned high tear resistance low smoke halogen-free sheath material comprises the following steps:
[0051] S1: The raw materials were mixed and plasticized in an internal mixer at 160°C for 15 minutes to obtain a processed material;
[0052] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; the temperature of zones 1 to 12 during twin-screw extrusion is 105° C., the temperature of the single-screw extruder during granulation is 135° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz;
[0053] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0054] Example 2
[0055] The high tear resistance low smoke zero halogen sheath material of this embodiment is prepared by the following raw materials in parts by weight:
[0056] 10 parts of ethylene vinyl acetate (EVA);
[0057] 3 parts of ethylene propylene diene monomer (EDPM), wherein the ethylene propylene diene monomer further contains 4 wt % of 5-ethylidene-2-norbornene;
[0058] 5 parts of linear low density polyethylene (LLDPE), wherein the linear low density polyethylene is selected from Exxon 3518CB;
[0059] 2 parts of eight-carbon polyolefin elastomer (eight-carbon POE);
[0060] 5 parts of maleic anhydride grafted polyethylene, the maleic anhydride grafted polyethylene is selected from Ju Ding 2002.
[0061] 75 parts of aluminum hydroxide and 5 parts of magnesium hydroxide;
[0062] 1 part of carbon forming agent hydrated magnesium silicate nano whisker, the hydrated magnesium silicate nano whisker is selected from whetstone mineral fiber hydrated magnesium silicate nanofiber, model is Adins Clay 20;
[0063] 1 part of an organic composite flame retardant, which is obtained by melt blending a polycarbonate-containing siloxane copolymer, an organic ammonium salt, a linear low-density polyethylene and calcium carbonate in a mass ratio of 1:1:3:75; the organic ammonium salt is selected from ammonium phosphate and ammonium polyphosphate; during melt blending, the internal mixer temperature is 120°C, and the single-screw extruder is used for extrusion granulation at 90°C.
[0064] 0.4 parts of an antioxidant, specifically pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate (DLTP) in a mass ratio of 2:1;
[0065] 0.3 parts of lubricant Struktol TR451.
[0066] The preparation method of the above-mentioned high tear resistance low smoke halogen-free sheath material comprises the following steps:
[0067] S1: The raw materials were mixed and plasticized in an internal mixer at 155°C for 12 minutes to obtain a processed material;
[0068] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; the temperature of zones 1 to 12 during twin-screw extrusion is 90° C., the temperature of the single-screw extruder during granulation is 120° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz;
[0069] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0070] Example 3
[0071] The high tear resistance low smoke zero halogen sheath material of this embodiment is prepared by the following raw materials in parts by weight:
[0072] 15 parts of ethylene vinyl acetate (EVA);
[0073] 5 parts of ethylene propylene diene monomer (EDPM), wherein the ethylene propylene diene monomer further contains 6 wt % of 5-ethylidene-2-norbornene;
[0074] 10 parts of linear low density polyethylene (LLDPE), wherein the linear low density polyethylene is selected from LG Chemical 3518CN;
[0075] 6 parts of eight-carbon polyolefin elastomer (eight-carbon POE);
[0076] 8 parts of maleic anhydride grafted polyethylene, the maleic anhydride grafted polyethylene is selected from Ju Ding 2002.
[0077] 85 parts of aluminum hydroxide and 10 parts of magnesium hydroxide;
[0078] 3 parts of carbon forming agent hydrated magnesium silicate nano whiskers, the hydrated magnesium silicate nano whiskers are selected from whetstone mineral fiber hydrated magnesium silicate nanofibers, model number is Adins Clay 20;
[0079] 3 parts of organic composite flame retardant, which is obtained by melt blending a polycarbonate-containing siloxane copolymer, an organic ammonium salt, a linear low-density polyethylene and calcium carbonate in a mass ratio of 1:1:3:75; the organic ammonium salt is selected from ammonium phosphate and ammonium polyphosphate; during melt blending, the internal mixer temperature is 120°C, and the single-screw extruder is 110°C for extrusion granulation.
[0080] 0.6 parts of antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and dilauryl thiodipropionate (DLTP), wherein the mass ratio of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and dilauryl thiodipropionate is 2:1.
[0081] 0.5 parts of lubricant Struktol TR451.
[0082] The preparation method of the above-mentioned high tear resistance low smoke halogen-free sheath material comprises the following steps:
[0083] S1: The raw materials were mixed and plasticized in an internal mixer at 165°C for 18 minutes to obtain a processed material;
[0084] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; the temperature of zones 1 to 12 during twin-screw extrusion is 120° C., the temperature of the single-screw extruder during granulation is 150° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz;
[0085] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0086] Comparative Example 1
[0087] The high tear resistance low smoke zero halogen sheath material of this comparative example is prepared by the following raw materials in parts by weight:
[0088] 20 parts of ethylene vinyl acetate (EVA);
[0089] 0 parts of ethylene propylene diene monomer (EDPM);
[0090] 10 parts of linear low-density polyethylene (LLDPE), wherein the linear low-density polyethylene is selected from Japan Pu Ruiman SP1520;
[0091] 4 parts of eight-carbon polyolefin elastomer (eight-carbon POE);
[0092] 6 parts of Nengzhiguang MC226 maleic anhydride grafted polyethylene;
[0093] 90 parts of aluminum hydroxide and 0 parts of magnesium hydroxide;
[0094] 0 parts of carbon forming agent;
[0095] 0 parts of organic compound flame retardant;
[0096] 0.5 parts of antioxidant, specifically pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate (DLTP) in a mass ratio of 2:1;
[0097] 0.4 parts of lubricant Struktol TR451.
[0098] The preparation method of the above-mentioned high tear resistance low smoke halogen-free sheath material comprises the following steps:
[0099] S1: The raw materials were mixed and plasticized in an internal mixer at 160°C for 15 minutes to obtain a processed material;
[0100] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; the temperature of zones 1 to 12 during twin-screw extrusion is 105° C., the temperature of the single-screw extruder during granulation is 135° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz;
[0101] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0102] Comparative Example 2
[0103] The high tear resistance low smoke zero halogen sheath material of this comparative example is prepared by the following raw materials in parts by weight:
[0104] 15 parts of ethylene vinyl acetate (EVA);
[0105] 5 parts of ethylene propylene diene monomer (EDPM);
[0106] 10 parts of linear low-density polyethylene (LLDPE), wherein the linear low-density polyethylene is selected from Japan Pu Ruiman SP1520;
[0107] 4 parts of eight-carbon polyolefin elastomer (eight-carbon POE);
[0108] 6 parts of Nengzhiguang MC226 maleic anhydride grafted polyethylene;
[0109] 90 parts of aluminum hydroxide and 0 parts of magnesium hydroxide;
[0110] 0 parts of carbon forming agent;
[0111] 0 parts of organic compound flame retardant;
[0112] 0.5 parts of antioxidant, specifically pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate (DLTP) in a mass ratio of 2:1;
[0113] 0.4 parts of lubricant Struktol TR451.
[0114] The preparation method of the above-mentioned high tear resistance low smoke halogen-free sheath material comprises the following steps:
[0115] S1: The raw materials were mixed and plasticized in an internal mixer at 160°C for 15 minutes to obtain a processed material;
[0116] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; the temperature of zones 1 to 12 during twin-screw extrusion is 105° C., the temperature of the single-screw extruder during granulation is 135° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz;
[0117] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0118] Comparative Example 3
[0119] The high tear resistance low smoke zero halogen sheath material of this comparative example is prepared by the following raw materials in parts by weight:
[0120] 15 parts of ethylene vinyl acetate (EVA);
[0121] 5 parts of ethylene propylene diene monomer (EDPM);
[0122] 10 parts of linear low-density polyethylene (LLDPE), wherein the linear low-density polyethylene is selected from Japan Pu Ruiman SP1520;
[0123] 4 parts of eight-carbon polyolefin elastomer (eight-carbon POE);
[0124] 6 parts of Nengzhiguang MC226 maleic anhydride grafted polyethylene;
[0125] 80 parts of aluminum hydroxide and 10 parts of magnesium hydroxide;
[0126] 0 parts of carbon forming agent;
[0127] 0 parts of organic compound flame retardant;
[0128] 0.5 parts of antioxidant, specifically pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate (DLTP) in a mass ratio of 2:1;
[0129] 0.4 parts of lubricant Struktol TR451.
[0130] The preparation method of the above-mentioned high tear resistance low smoke halogen-free sheath material comprises the following steps:
[0131] S1: The raw materials were mixed and plasticized in an internal mixer at 160°C for 15 minutes to obtain a processed material;
[0132] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; the temperature of zones 1 to 12 during twin-screw extrusion is 105° C., the temperature of the single-screw extruder during granulation is 135° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz;
[0133] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0134] Comparative Example 4
[0135] The high tear resistance low smoke zero halogen sheath material of this comparative example is prepared by the following raw materials in parts by weight:
[0136] 15 parts of ethylene vinyl acetate (EVA);
[0137] 5 parts of ethylene propylene diene monomer (EDPM);
[0138] 10 parts of linear low-density polyethylene (LLDPE), wherein the linear low-density polyethylene is selected from Japan Pu Ruiman SP1520;
[0139] 4 parts of eight-carbon polyolefin elastomer (eight-carbon POE);
[0140] 6 parts of Nengzhiguang MC226 maleic anhydride grafted polyethylene;
[0141] 80 parts of aluminum hydroxide and 8 parts of magnesium hydroxide;
[0142] 2 parts of carbon forming agent hydrated magnesium silicate nano whisker, the hydrated magnesium silicate nano whisker is selected from whetstone mineral fiber hydrated magnesium silicate nanofiber, model is Adins Clay 20;
[0143] 0 parts of organic compound flame retardant;
[0144] 0.5 parts of antioxidant, specifically pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate (DLTP) in a mass ratio of 2:1;
[0145] 0.4 parts of lubricant Struktol TR451.
[0146] The preparation method of the above-mentioned high tear resistance low smoke halogen-free sheath material comprises the following steps:
[0147] S1: The raw materials were mixed and plasticized in an internal mixer at 160°C for 15 minutes to obtain a processed material;
[0148] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; the temperature of zones 1 to 12 during twin-screw extrusion is 105° C., the temperature of the single-screw extruder during granulation is 135° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz;
[0149] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0150] Comparative Example 5 (Traditional Group)
[0151] The high tear resistance low smoke zero halogen sheath material of this comparative example is prepared by the following raw materials in parts by weight:
[0152] 20 parts of ethylene vinyl acetate (EVA);
[0153] 0 parts of ethylene propylene diene monomer (EDPM);
[0154] 14 parts of linear low-density polyethylene (LLDPE), wherein the linear low-density polyethylene is selected from Japan Pu Ruiman SP1520;
[0155] 0 parts of eight-carbon polyolefin elastomer (eight-carbon POE);
[0156] 6 parts of Nengzhiguang MC226 maleic anhydride grafted polyethylene;
[0157] 90 parts of aluminum hydroxide and 0 parts of magnesium hydroxide;
[0158] 0 parts of carbon forming agent;
[0159] 0 parts of organic compound flame retardant;
[0160] 0.5 parts of antioxidant, specifically pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and dilauryl thiodipropionate (DLTP) in a mass ratio of 2:1;
[0161] 0.4 parts of lubricant Struktol TR451.
[0162] The preparation method of the above-mentioned high tear resistance low smoke halogen-free sheath material comprises the following steps:
[0163] S1: The raw materials were mixed and plasticized in an internal mixer at 160°C for 15 minutes to obtain a processed material;
[0164] S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; the temperature of zones 1 to 12 during twin-screw extrusion is 105° C., the temperature of the single-screw extruder during granulation is 135° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz;
[0165] S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
[0166] Table 1 Formula data of each embodiment and comparative example
[0167] Traditional Group Control group 1 Control group 2 Control group 3 Control group 4 Example 1 Ethylene-vinyl acetate copolymer 20 20 15 15 15 15 EPDM - - 5 5 5 5 Linear low density polyethylene 14 10 10 10 10 10 Eight-carbon polyolefin elastomer - 4 4 4 4 4 Maleic anhydride grafted polyethylene 6 6 6 6 6 6 Aluminum hydroxide 90 90 90 80 80 80 Magnesium hydroxide - - - 10 8 8 Carbon forming agent - - - - 2 2 Organic compound flame retardant - - - - - 0.8 Antioxidants 0.5 0.5 0.5 0.5 0.5 0.5 Lubricants 0.4 0.4 0.4 0.4 0.4 0.4
[0168] Effect evaluation 1
[0169] The high tear resistance low smoke zero halogen sheath material of each embodiment and comparative example was preheated for 5 minutes in a flat vulcanizer with a pressure of 18±2MPa, pressurized at 170±5℃ for 5 minutes, cooled and pressurized for 5 minutes to obtain a sample; finally, the test was carried out according to the test items. The test method was tested according to GB / T 32129-2015 standard; the tear strength was tested according to GB / T 16578.1-2008 standard.
[0170] Table 2 Performance test data of each embodiment and comparative example
[0171]
[0172] The products of various embodiments of the present invention can meet the following standard indicators and requirements:
[0173] Density: ≤1.55g / cm 3 , tensile strength: ≥10MPa, elongation at break: ≥160%, thermal stress cracking resistance (130℃*1h*7kg): qualified; limiting oxygen index: ≥38%, tear resistance: ≥15N / mm.
[0174] The traditional group and comparative example 1 show that the overall toughness of the material is improved by adding the eight-carbon polyolefin elastomer, and the elongation is significantly improved;
[0175] Comparative Examples 1 and 2 show that the tear strength and elongation of EPDM rubber materials are significantly improved;
[0176] Comparative Examples 2 and 3 show that although the elongation is reduced by 10% when magnesium hydroxide is added, the tensile strength and tear resistance of the material are improved;
[0177] Comparative Examples 3 and 4 show that the addition of the carbon forming agent does not reduce other properties, and the oxygen index increases by 1%;
[0178] Comparison of Comparative Example 4 with Example 1 shows that the oxygen index is increased by 2% by adding the organic compound flame retardant.
[0179] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A high tear resistance low smoke halogen-free sheath material, characterized in that: By weight, it is prepared by the following raw materials: The carbon forming agent comprises hydrated magnesium silicate nano whiskers; the organic composite flame retardant is obtained by melt blending a siloxane copolymer containing polycarbonate, an organic ammonium salt, a linear low-density polyethylene and calcium carbonate; the organic ammonium salt is selected from ammonium phosphate and ammonium polyphosphate.
2. The high tear resistance low smoke zero halogen sheath material according to claim 1, characterized in that: The EPDM rubber also contains 5 wt% of 5-ethylidene-2-norbornene.
3. The high tear resistance low smoke zero halogen sheath material according to claim 1, characterized in that: The organic ammonium salt is selected from ammonium phosphate and ammonium polyphosphate.
4. The high tear resistance low smoke zero halogen sheath material according to claim 1, characterized in that: In the organic composite flame retardant, the mass ratio of the polycarbonate-containing siloxane copolymer, the organic ammonium salt and the linear low-density polyethylene is 2:2:
6.
5. The high tear resistance low smoke zero halogen sheath material according to claim 1, characterized in that: The antioxidant is selected from pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and dilauryl thiodipropionate.
6. The high tear resistance low smoke zero halogen sheath material according to claim 1, characterized in that: During the melt blending, the internal mixer temperature is 120° C., and the single screw extruder is used for extrusion granulation at 90-110° C.
7. A method for preparing the high tear resistance low smoke zero halogen sheath material according to any one of claims 1 to 6, characterized in that: The steps include: S1: Mixing and plasticizing the raw materials in an internal mixer to obtain processed materials; S2: After the processed material is extruded through a twin-screw extruder, it is granulated through a single-screw extruder to obtain sheath raw material particles; S3: conveying the sheath raw material particles through air cooling, and packaging to obtain the high tear resistance, low smoke, and halogen-free sheath material.
8. The preparation method according to claim 7, characterized in that: In the step S1, the temperature of mixing and plasticizing in the internal mixer is 155-165° C., and the time of mixing and plasticizing is 12-18 minutes.
9. The preparation method according to claim 7, characterized in that: In the step S2, the temperature of zones 1 to 12 of the twin-screw extruder during extrusion is 90-120° C.; the temperature of the single-screw extruder during granulation is 120-150° C., and the pelletizing frequency of the single-screw extruder is 1200 Hz.
10. A cable sheath, characterized in that: The sheath is prepared by using the high tear resistance, low smoke and halogen-free sheath material described in any one of claims 1 to 6.